Prastudi Pembentukan Magister Terapan Bidang Penerbangan di Indonesia - Imam Sonhaji; Sri Rahayu Surtiningtas; Ichyu Machmiyana (Politeknik Penerbangan Makassar, 2022)
The COVID-19 pandemic demands changes in all aspects of aviation to create programs to mitigate risks, so that competence in the field of health, safety, and environment (HSE) is required through an applied master's program. This study aims to obtain information about the interest of flight personnel to continue their study of the applied master's program, obtain an overview of the readiness to implement the applied master's program, and get information on the map of the needs of users of applied master's graduates at PPI Curug. The research method is combined namely quantitative and qualitative methods. Using surveys with flight personnel research objects, data collection is carried out by questionnaires and Focus Group Discussions (FGD). The results of this research are that the opening of the Applied Masters Study Program received high enthusiasm from prospective participants/students, the readiness of PPI Curug in the infrastructure, curriculum, and dan unit pengelola program studi (UPPS) is sufficient but requires the addition of 3 educators with doctoral qualifications (S3), and prospective graduate users welcome and support because the resulting graduate profile is in line with industry needs.